2020
DOI: 10.5154/r.rchsza.2021.19.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribución potencial de Euphorbia antisyphilitica Zucc. en México

Abstract: El conocimiento de la distribución de las especies en relación con las condiciones bióticas y abióticas permite conocer las posibles respuestas de las especies a los cambios, ubicar la presencia geográfica de especies de importancia comercial. Los objetivos fueron Identificar las variables bioclimáticas que determinan la distribución de poblaciones de E. antisyphilitica y estimar la distribución potencial de la especie en las zonas áridas usando dos métodos Maxent y Bioclim. Los datos de presencia fueron del i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(53 reference statements)
0
2
1
Order By: Relevance
“…The mean temperature of the coldest quarter (BIO 11) showed a mean of 12.8 • C and a contribution of 6.9% of the total variability of the model, in comparison to the study of Hernández-Herrera et al [55], where the contribution was 0.3%. The variable has a crucial role in the establishment and development of plant species in arid regions.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The mean temperature of the coldest quarter (BIO 11) showed a mean of 12.8 • C and a contribution of 6.9% of the total variability of the model, in comparison to the study of Hernández-Herrera et al [55], where the contribution was 0.3%. The variable has a crucial role in the establishment and development of plant species in arid regions.…”
Section: Discussioncontrasting
confidence: 57%
“…In the studies of Bañuelos-Revilla et al [47] and Vargas-Pineda et al [51], the variable BIO 12 showed 4.7% and 4.5% of the total contribution of the model to predict the distribution of candelilla in Mexico, which was compared with the 21.9% obtained in the present study. The results of the previous studies are lower, but it has been confirmed that the annual precipitation is of importance for the presence of candelilla at the national scale [55].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation